Functional structure of European forest beetle communities is enhanced by rare species. (March 2022) - Burner, Ryan C.; Drag, Lukas; Stephan, Jörg G.; Birkemoe, Tone; Wetherbee, Ross; Muller, Jörg; Siitonen, Juha; Snäll, Tord; Skarpaas, Olav; Potterf, Mária; Doerfler, Inken; Gossner, Martin M.; et al.
Abstract: Biodiverse communities have been shown to sustain high levels of multifunctionality and thus a loss of species likely negatively impacts ecosystem functions. For most taxa, however, roles of individual species are poorly known. Rare species, often most likely to go extinct, may have unique traits and functional roles. Alternatively, rare species may be functionally redundant, such that their loss would not disrupt ecosystem functions. We quantified the functional role of rare species by using captures of wood-living (saproxylic) beetle species, combined with recent databases of morphological and ecological traits, from three regions in central and northern Europe. Using a rarity index based on species' local abundance, geographic range, and habitat breadth, we used local and regional species removal simulations to examine the contributions of both the rarest and the most common beetle species to three measures of community functional structure: functional richness, functional specialization, and functional originality. Both regionally and locally, all three measures declined more rapidly when rare species were removed than under common (or random) species removal scenarios. These consistent patterns across scales and among forest types give evidence that rare species provide unique functional contributions, and their loss may disproportionately impact ecosystem functions. This implies that conservation measures targeting rare and endangered species, such as preserving intact forests with dead wood and mature trees, can provide broader ecosystem-level benefits. Experimental research linking functional structure to ecosystem processes should be prioritized to increase understanding of the functional consequences of species loss and to develop more effective conservation strategies.